Lori Ann Ellis 'Missing Women's Commission of Inquiry' Testimony 1 - Ellis, Lori Ann; Interviewer: Barnes, Louise; Oral Testimony Archivist(s) - Harrison, Donny; Principle Investigator: ross, Dr. annie (Simon Fraser University, 2012)
Disclaimer: All testimonies are the experiences and beliefs of the individuals interviewed.